2015
DOI: 10.1038/srep16394
|View full text |Cite
|
Sign up to set email alerts
|

Interface-designed Membranes with Shape-controlled Patterns for High-performance Polymer Electrolyte Membrane Fuel Cells

Abstract: Polymer electrolyte membrane fuel cell is a promising zero-emission power generator for stationary/automotive applications. However, key issues, such as performance and costs, are still remained for an economical commercialization. Here, we fabricated a high-performance membrane electrode assembly (MEA) using an interfacial design based on well-arrayed micro-patterned membranes including circles, squares and hexagons with different sizes, which are produced by a facile elastomeric mold method. The best MEA per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 41 publications
2
53
0
1
Order By: Relevance
“…This became in particular evident using electrodes with low Pt-loading, where at high current densities a strong deviation was observed between a CCM and DMD sample in the iR-free representation. In recent literature new concepts with patterned membranes revealed that in spite of identical membrane thickness a modified catalystemembrane interface can strongly improve the cell performance [28,29]. These observations are in good agreement with the observed characteristics of DMD fuel cells.…”
Section: Resultssupporting
confidence: 86%
“…This became in particular evident using electrodes with low Pt-loading, where at high current densities a strong deviation was observed between a CCM and DMD sample in the iR-free representation. In recent literature new concepts with patterned membranes revealed that in spite of identical membrane thickness a modified catalystemembrane interface can strongly improve the cell performance [28,29]. These observations are in good agreement with the observed characteristics of DMD fuel cells.…”
Section: Resultssupporting
confidence: 86%
“…[1][2][3][4] Among many different fuel cells, solid oxide fuel cell (SOFC) is one of the most promising electric power generator for delivering high electrical and fuel regeneration efficiency. [5][6][7][8] SOFC is composed from a dense electrolyte layer that is sandwiched between two porous electrodes of cathode and anode.…”
Section: Introductionmentioning
confidence: 99%
“…This was linked to an improved interface between catalyst layers and membrane. [43,47] In previous work, this low R LF-HF was related to strong water Adv. [43,47] In previous work, this low R LF-HF was related to strong water Adv.…”
Section: Beginning Of Test/ End Of Test -Analysismentioning
confidence: 85%